Tháıdene Yatı Hóneneltën (Ancestral Dene Language Pedagogies) — Dene Dedlıne Yatı Acquisition, Revitalization and Reclamation - Napier, Kyle (2020)
Dene Dedlıne Yatı is an ancient Dene language which has been minimally addressed by linguists outside of reference to /t/-dialect Dënesųłı̨né. Like most Indigenous Peoples on this continent, Dene Dedlıne face ongoing shifts impacting connection to lands and languages. This work prioritizes the voices of speakers of Dene Dedlıne Yatı to support Dene Dedlıne Yatı acquisition, revitalization and reclamation which is specific to Dene learning Dene Dedlıne Yatı in Tu Nedhé. Interviews were held with Elders, knowledge holders and learners from Tu Nedhé who distinguished Dene Dedlıne Yatı through its historical paths, addressed the catalysts of trauma against Dene Dedlıne lands and languages, and provided solutions to reversing language shift as voiced by Dene Dedlıne. These interviews also resulted in recommendations to federal, territorial and Indigenous governments; communities, such as schools and resource developers; and to the family unit, including speakers, learners and the family itself. This collaborative work illustrates the importance of Dene-led Dene Dedlıne Yatı acquisition, revitalization and reclamation programming in Tu Nedhé.